Analyzing characteristics of knock in a hydrogen-fueled Wankel rotary engine. (1st July 2022) - Meng, Hao; Ji, Changwei; Su, Teng; Yang, Jinxin; Chang, Ke; Xin, Gu; Wang, Shuofeng
Abstract: Hydrogen-fueled Wankel rotary engine (HWRE) as a promising power device overcomes some of the drawbacks of the hydrogen-fueled reciprocating engine. However, its elongated combustion chamber makes it prone to knock, and little research has been done in this area. Hence, to understand the knock characteristics of HWRE, the present work focus on parameters of HWRE knock at 2000r/min, an excess air ratio of 1.2 and an ignition timing of −7°CA ATDC. The main results are as follows: As with knock intensity, knock duration and maximum pressure rising rate also can characterize the knock of HWRE because of the logarithmic or linear relationship among three parameters. For the knock intensity, two parameters are needed to precisely characterize the HWRE knock, while only one parameter is needed for the knock duration and the maximum pressure rising rate. Considering the computing cost, the maximum pressure rising rate is better than others. The knock intensity has a significant influence on the timed sequence of peak knock pressure and peak in-cylinder pressure. Besides, the mechanism of backfire caused by the knock of HWRE is different from that of the hydrogen-fueled reciprocating piston engine, which results from the inter-cylinder flame leakage. Highlights: The knock characteristic of hydrogen-fueled Wankel rotary engine is analyzed. There are mathematical relationships among parameters characterizing knock. Maximum pressure rise rate is a better metric to characterize WRE knock. Misfire caused by knock in WRE is different from reciprocating piston engines.